Drug repurposing in autosomal dominant polycystic kidney disease: back to the future with pioglitazone - Mao, Zhiguo (Clin Kidney J, 2021)
Autosomal dominant polycystic kidney disease (ADPKD) is the most common inherited cause of end-stage kidney failure. At present, only one drug, tolvaptan, has been approved for use to slow disease progression, but its use is limited by reduced tolerability and idiosyncratic liver toxicity. Thiazolidinediones were first developed as insulin-sensitizers but also regulate gene transcription in multiple tissues, leading to systemic effects on metabolism, inflammation and vascular reactivity. In this issue, Blazer-Yost et al. report the results of a single-centre Phase 1b double-blind placebo-controlled crossover study of the peroxisome proliferator-activated receptor γ (PPAR-γ) agonist pioglitazone in 18 ADPKD patients. Encouragingly, there were no major safety signals, although evidence of efficacy could not be demonstrated due to the small sample size. We review the preclinical evidence for the use of PPAR-γ agonists in ADPKD and speculate on the likely beneficial and adverse clinical effects of this interesting class of compounds in a future trial.